Karakteristik Ekstrak Kulit Biji Kakao (Theobroma cacao L.) sebagai Sumber Antioksidan pada Perlakuan Ukuran Partikel dan Waktu Maserasi - Rahmadhani, Reren; Ganda Putra, G.P.; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 2 (2020): Juni, 2020)
Cocoa beans husk is the highest waste of the cocoa fruit processing and has not been used optimally. The waste of coco a beans husk contain polyphenol that can be used for antioxidants. Polyphenol on beans husk of cocoa can be extract using extraction method. This study aims were to determine the effect of the macerations and particle size o n the extract beans husk of cocoa as a source of antioxidants and to determine the best of solvent concentration and particle size to produce extract of beans husk of cocoa a source of antioxidant. The study was the experimental research which designed by using randomized block desin (RBD) with two factors. The first factor was particle size that that consists of 40, 60 and 80 mesh. The second factor was maceration time, wich were done for  24, 36 and 48 hours.  The data were analyzed by analysis of variance (ANOVA) and continued with the Tukey test. The results showed that maceration time and particl e size had a very significant effect on yield, total phenolics and antioxidant capacity o n the extract of beans husk of cocoa. Interactions between treatments had a very signifiacant effect on total phenolic and antioxidant capacity but significantly effect the yield on the extract of beans husk of cocoa. 80 mesh of particle size and 48 hours maceration time was thebest treatment for extracting beans husk of cocoa as a source of antioxidants with characteristic 14.28±0.7 percent of yields, 92.2 ±1.66 mg GAE/g of total phenolics , and 57.71±0.27 mg GAEAC/g of antioxidant capacity . Keywords : cocoa beans husk , extraction, particle size, antioxidants.